Promosi Budaya Dugderan Melalui Konten Akun @Disbudparkotasemarang Sebagai Promosi Wisata Kota Semarang - Rosalia, Naiza; Mukaromah, Mukaromah; Amalia Hapsari, Swita (Avant Garde, 2023)
Instagram as a social media platform is in second place as the most popular social media in Indonesia. Therefore, many institutions and companies use social media to distribute information and promote their events or services. The Semarang City Culture and Tourism Office chose to use social media to manage information services to the public. One of them is when promoting cultural events taking place in the city of Semarang. Dugderan, as an annual cultural event held in Semarang City, is also promoted on the Instagram account @disbudparkotasemarang. This research aims to find out how the Semarang City Culture and Tourism Department promotes the Dugderan event using the SAVE Models theory (Solution, Access, Value, Educate), this research is to find out content strategies that show the framing of Dugderan culture in Semarang City through content on the account @ disbudparkotasemarang. To obtain primary data, this research used an in-depth interview method. Meanwhile, to collect secondary data, this research uses library research and documentation. The results of this research show that the Instagram account of the Semarang City Culture and Tourism Office promotes Dugderan and provides sufficient information in terms of the SAVE MODEL concept, although there is some information that needs to be added, such as what the benefits are for tourists or residents from coming to the event and other added value. so that this Dugderan event is promoted in accordance with the targets of theDisbudpar of Semarang City